2020
DOI: 10.1186/s43055-020-00182-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond fetal magnetic resonance diagnosis of corpus callosum agenesis

Abstract: Background Corpus callosum agenesis (CCA) is a midline congenital anomaly. Routine prenatal 2D ultrasonography (2D US) can suggest CCA. A definitive diagnosis and identification of more subtle associated neurological or non-neurological abnormalities are difficult to be detected by prenatal 2D US; therefore, a further study by fetal magnetic resonance imaging (MRI) is needed. This study highlights the role and evaluates the diagnostic value of fetal MRI in the diagnosis of CCA and identifying the associated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 17 publications
6
9
1
Order By: Relevance
“…Comparing the results of the above‐mentioned studies 62–64 might suggest that MRI is less helpful in detecting associated anomalies when an isolated ACC is suggested by US. Moreover, in D'Antonio et al's study, related anomalies were found only at birth and missed at both prenatal US and MRI in 3.9% of cases 64 .…”
Section: Role Of Mrimentioning
confidence: 98%
See 4 more Smart Citations
“…Comparing the results of the above‐mentioned studies 62–64 might suggest that MRI is less helpful in detecting associated anomalies when an isolated ACC is suggested by US. Moreover, in D'Antonio et al's study, related anomalies were found only at birth and missed at both prenatal US and MRI in 3.9% of cases 64 .…”
Section: Role Of Mrimentioning
confidence: 98%
“…Sotiriadis et al showed that MRI can find additional abnormalities in 22.5% of cases of ACC, compared to US, especially for cortical malformations and heterotopies 36 . Ibrahim et al in a study performed on 27 fetuses suspected of ACC on a prenatal US, reported 100% and 75% for fetal MRI and 2D US regarding the sensitivity of the detection of associated neurological abnormalities, respectively 62 . Recently, D'Antonio et al investigated prenatal MRI role in fetuses with CC isolated anomalies in US and showed that MRI can identify 11.2% of additional anomalies which were mainly the malformations of cortical development (Figure 16).…”
Section: Role Of Mrimentioning
confidence: 99%
See 3 more Smart Citations